Endoscopic elimination of foreign body from the upper gastrointestinal tract in Republican Vilnius university hospital: 25 years’ experience - Kildušis, Edvinas; Grigaliūnas, Aurelijus; Žilevičė, Laura (Lietuvos chirurgija, 2018)
[full article and abstract in Lithuanian; abstract in English] Foreign body and food bolius impaction in the upper gastrointestinal tract is a common clinical situation in emergency departments throughout the world. The majority of foreign bodies will pass through the gastrointestinal tract and naturally go out with the stool, but in about 1/5 of cases the foreign bodies must be removed. The impaction of a foreign body in the upper gastrointestinal tract is the second leading cause of urgent endoscopy after bleeding. The aim of this retrospective descriptive study is to review a quarter-century (25 years) experience of removal foreign bodies from the upper gastrointestinal tract by flexible endoscopic approach in Republican Vilnius University Hospital (RVUL). We conclude that the endoscopic removal of foreign bodies by a qualified specialist is an effective and safe method with a great success rate of the procedure using an endoscope with accessories: loop, basket and forceps, which significantly reduces the length of hospitalization and requirement of surgery.